Association between risk of ischemic stroke and liver enzymes levels: a systematic review and meta-analysis - Omnia Samy El-Sayed; Asmaa Zakria Alnajjar; Abdelfattah Arafa; Hazem E. Mohammed; Abdelrahman M. Elettreby; Safiya Ibraheem; Dalia Esam Tawfik; Menna Allah Ashraf Abdullah; Mohamed Ahmed Tolba (BMC Neurology)
Abstract Background Ischemic stroke is a major public health concern, contributing significantly to global morbidity and mortality. Recent studies have suggested that alterations in liver enzymes may be linked to the risk of developing a stroke. However, the relationship between liver enzymes and ischemic stroke remains unclear. Objective To examine the potential role of liver enzymes as biomarkers for ischemic stroke. Methods We systematically searched four databases for articles investigating the association between liver enzymes and ischemic stroke up to March 20th, 2024. Newcastle Ottawa Scale judged the quality of included studies. Risk ratio (RR), hazard ratio (HR), or odds ratio (OR) were extracted and statistically analyzed by RevMan and R software. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) assessed the certainty of evidence. Results Increased levels of gamma-glutamyl transferase (GGT) and alkaline phosphatase (ALP) have shown statistically significant association with increased ischemic stroke risk (RR: 1.43, 95% CI: [1.30 to 1.57], P > 0.00001) and (RR: 1.60, 95% CI: [1.22 to 2.10], P = 0.0006), respectively. Conversely, increased levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) showed no significant association with ischemic stroke risk (RR: 0.92, 95% CI: [0.68 to 1.24], P = 0.58) and (RR: 1.43, 95% CI: [0.83 to 2.49], P = 0.20), respectively. The evidence for all outcomes had a low or very low level of certainty. Conclusion GGT and ALP could be potential biomarkers for increased ischemic stroke risk, which necessitates careful follow-up. However, AST and ALT did not show such association.